Actinomyces infection causing acute right iliac fossa pain. (28th May 2014) - Govindarajah, Narendranath; Hameed, Waseem; Middleton, Simon; Booth, Michael
Abstract : This is a case of a 75-year-old man being admitted to the on-call surgical department with acute abdominal pain. On arrival he was clinically dehydrated and shocked with localised pain over McBurney's point and examination findings were suggestive of appendiceal or other colonic pathology. Full blood testing revealed a white cell count of 38×10 9 /L and a C reactive protein (CRP) of 278 mg/L. A CT scan revealed a gallbladder empyema that extended into the right iliac fossa. This case highlights the potential for a hyperdistended gallbladder empyema to present as acute right iliac fossa pain with blood tests suggestive of complicated disease. Further analysis confirmed Actinomyces infection as the underlying aetiology prior to a laparoscopic subtotal cholecystectomy. This case serves to remind clinicians of this as a rare potential cause of atypical gallbladder pathology.